SECONDARY RECRYSTALLIZATION OF MOLYBDENUM SHEET DOPED WITH CAO AND MGO UNDER HYDROGEN ATMOSPHERE - YOO, MK; HIRAOKA, Y; CHOI, J (ELSEVIER SCI LTD, 1995)
The recrystallization of Mo sheet doped with CaO and MgO under a H-2 atmosphere containing O-2 was investigated by means of optical, scanning-and transmission-electron microscopies. Also, in order to understand the chemical doping process, dried doping-reagent (Ca,Mg)(NO3)(2) was thermally decomposed and analyzed by DTA and TGA methods. X-ray diffraction scanning was used to identify the thermally decomposed products. During presintering at 1000 degrees C for 3.6 x 10(3) s, the doping reagent changed into CaO, MgO and Ca(OH)(2). Upon sintering the presintered compact at 2000 degrees C under a He (inert) atmosphere, MoO2 was formed by internal oxidation. However, under H-2 (reduction) atmospheres, the particles including Ca, Mg, Si and Al were observed. For the sheet, etch pits in a row (indicating low-angle boundaries) were observed along the primary grain boundaries within the coarsened grain at the beginning of the secondary recrystallization. Ln addition, the coarse particles containing Ca, Mg, Si and Al were also observed during the secondary recrystallization and the decrease of oxygen was not recognized. These results suggest that the coalescence of primary grains and the coarsening of dopant particles play an important role during the secondary recrystallization under a H-2 atmosphere.
Keywords: SINGLE-CRYSTAL; TEMPERATURE